Sebaran Data Anak-Anak Berkebutuhan Khusus di Kota Lubuklinggau Berbasis WEB GIS - A. Taqwa Martadinata; Joni Karman (LPPM STIKOM Tunas Bangsa, 2023)
The problems in this study are: (a) How researchers designed geographic location information systems for the distribution of data on children with special needs equipped with information services that are friendly to them. (b) How the application can be Implemented and used easily. In addition, the purpose of this study is to design a geographic information system application for the distribution of locations of children with special needs based on WebGIS in Lubuklinggau and to apply knowledge about information systems theoretically and practically. In addition, this research method is descriptive using the waterfall method which consists of several stages: analysis, design, coding and testing. Furthermore, in collecting data, researchers use primary data and secondary data. So it is hoped that later this designed application will apply web service technology, so that information about mapping children with special needs is always up to date. And to overcome this problem, researchers use an approach to a digital mapping model in the form of a Web-based GIS by utilizing leafleat.js as a digital map. The method used in this study uses UML (Unifed Modeling Language), PHP programs, codeigniter frameworks and MySQL databases as data storage. The Geographic Information System (GIS) for the distribution of children with special needs (ABK) aims to provide convenience and speed to children with special needs in obtaining information about health and public facilities services that are friendly to those in Lubuklinggau City.